The Influences of Profitability and CSR on Tax Aggressiveness in FnB in 2021-2024 - Meyrestu Suci Dasniati; Nugraeni Nugraeni (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
This research aims to examine the influence of profitability and CSR on the level of tax aggressiveness in food and beverage companies listed on Bursa Efek Indonesia (IDX) during the 2021-2024 period. The research background is based on the tendency of companies to accelerate tax efficiency through various possible motives of tax aggressiveness practices. The method used in this study is a quantitative approach with a documentation collection technique and a sample selection process with a purposive sampling technique, which produces 68 observation data. For data analysis, ETR, ROA, multiple linear regression, classical assumption testing, and others, accompanied by hypothesis testing. The findings of this study reveal that profitability has a negative influence on tax aggressiveness, which means that the level of profitability was the high in the company, the higher the tendency to engage in tax aggressiveness. However, CSR has not shown a significant effect on aggressiveness of tax. These findings make it explains that the implementation of CSR has no direct relationship with aggressive tax management practices.